Gas chromatography : biochemical, biomedical, and clinical applications - Clement, Ray E (John Wiley and Sons, 1990)
Concerned with the use of gas chromatography to solve biological and biochemical problems. Provides thorough coverage of the methods involved--basic principles and equipment, multidimensional techniques, detectors and derivatization techniques. Several chapters deal specifically with biological applications such as the biological profiling and monitoring of drug therapy, and the detection of urinary acids and steroids, prostaglandins, fatty acids and lipids. Treats drug abuse detection, toxicological problems and the determination of heavy metals in blood plasma. The use of gas chromatography for identifying bacteria in the clinical microbiology laboratory is also discussed.
Chemical analysis ; Vol. 111
Keywords: chemie, klinická chemie; Chromatography, Gas; chromatografie plynová